Die Logik der Schulmathematik Neue Grunderkenntnisse und neue Denkhürden - Assing, Helmut (Wissenschaftliche Buchgesellschaft (wbg), 2023)
The book is the first systematic and all-round scientific attempt to research the logical rules used in school mathematics in depth. This revealed an important peculiarity: In school mathematics - unlike in the science of mathematics and unlike in the other sciences - two logical systems, that of colloquial language and the artistic logical system founded by G. Frege, enter into a relationship that is hardly known. In the book, this is particularly demonstrated in the work of Ch. Schamberger and the "goat problem". The first efforts of the book brought several not unimportant partial results, but above all revealed larger gaps in the research of colloquial logic. In the future, this and the formation of new logic systems (e.g. of a quantum logic type) will be of the utmost importance.